Theater, caberet and concert programs of the French POW camp Bizerte in Tunisia. . From 'Kriegsgefangenenlager Bizerte Collection'
Theater, caberet and concert programs of the French POW camp Bizerte in Tunisia. From 'Kriegsgefangenenlager Bizerte Collection'.